Nursing care in patients with severe preeclampsia - Espiritu-Gozar, Nancy; Heredia-Garay, Flor M.; Cabanillas-Chavez, María Teresa; Morales-García, Wilter C. (SCT Proceedings in Interdisciplinary Insights and Innovations, 2024)
Introduction: Preeclampsia is a pregnancy and postpartum complication characterized by high blood pressure, being one of the most important public health problems; multisystem pathology of great variable severity, which may not present symptoms at the beginning; however, it can cause serious and even fatal complications for the mother and fetus. Objectives: To know the nursing care in patients with severe preeclampsia. Methodology: Qualitative study, with a single case design based on the nursing care process method, applying the functional pattern assessment guide according to Marjorie Gordon to a 34-year-old primiparous pregnant woman with data from the clinical history, the interview, physical examination, and taxonomies (NANDA, NOC, NIC) that were used to formulate care plans. Results: 9 nursing diagnoses with altered patterns were found, only one main diagnosis was prioritized: ineffective peripheral tissue perfusion r/c insufficient knowledge of the disease process with a problem associated with hypertension evidenced by edema, were the interventions performed satisfactory in the pregnant woman, before the CP gestational hypertension and the CR malignant hypertension, being the results defined by the time of intervention and evaluation. Discussion: To conclude as specialist professionals we must make a good assessment and avoid any risk of complications in the pregnant woman. Due to the care provided in the gynecological emergency to the maternal-fetal binomial, a progressive evolution is observed with the preparation to be referred to the operating room. Conclusions: Nursing care in clinical practice is very important when applying the nursing process that strengthens the autonomy of nursing in patients with severe preeclampsia, since the professional specialist in obstetrics and gynecology provides quality standards.